Diazepam influences urinary bioindicator of occupational toluene exposure - Silveira, Alberto Thalison; Albuquerque, Ana Carolina Campos; Lepera, Jose Salvador [UNESP]; Martins, Isarita (Elsevier B.V., 2016)
In the present study, we investigated the influence of diazepam (DZP) on the excretion of TOL by examining their urinary metabolites, hippuric acid (HA) and ortho-cresol (o-C). Male Wistar rats were exposed to TOL (20 ppm) in a nose-only exposure chamber (6 h/day, 5 days/week for 6 weeks) with simultaneous administration of DZP (10 mg/kg/day). Urinary o-C levels were determined by GC MS, while HA, creatinine (CR), DZP and its metabolite, nordiazepam, were analysed by HPLC-DAD. The results of a Mann-Whitney U test showed that DZP influenced the urinary excretion of o-C (p < 0.05). This pioneering study revealed that there was an interaction between DZP and TOL, probably by the inhibition of the CYP isoforms (CYP2B6, CYP2C8, CYP2E1, and CYP1A2) involved in the oxidative metabolism of the solvent. ThiS is relevant information to be considered in the biomonitoring of occupational toluene exposure. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Toluene; Diazepam; Occupational exposure; o-Cresol; Hippuric acid